Integrating Multidisciplinary Approaches to Strengthen Community Health Outcomes: A Qualitative Perspective - Prasetyowati Prasetyowati; Kaharto Kaharto (Journal Interdisciplinary Health, 2026)
Introduction: Community health outcomes continue to face complex challenges driven by the interaction of biomedical, social, economic, environmental, and behavioral determinants. Fragmentation across health disciplines often limits the effectiveness and sustainability of community health interventions. Integrating multidisciplinary approaches has been increasingly promoted to address these challenges; however, empirical evidence explaining how such integration operates in community-based settings remains limited, particularly from a qualitative perspective. Methods: This study employed a qualitative research design using an exploratory and interpretive approach. Data were collected through in-depth interviews, focus group discussions, and document reviews involving purposively selected stakeholders engaged in multidisciplinary community health initiatives. Thematic analysis was conducted to identify key patterns, processes, and contextual factors influencing multidisciplinary integration. Results: The findings revealed that effective multidisciplinary collaboration is shaped by shared goals, role clarity, communication practices, and meaningful community engagement. Socio-cultural and institutional contexts were found to significantly influence how collaboration is enacted in practice. Participants perceived that multidisciplinary integration improved coordination, reduced service fragmentation, and enabled a more holistic response to community health needs. Conclusion: This study concludes that multidisciplinary approaches strengthen community health outcomes by fostering coordinated, context-sensitive, and people-centered health interventions. Qualitative insights highlight the importance of relational and contextual factors in sustaining effective multidisciplinary collaboration in community health systems.